STRUCTURAL PERFORMANCE EVALUATION OF STONE MASTIC ASPHALT MIXTURE WITH POLYMER MODIFIED ASPHALT - PLASTOMER ORIENTED (ETHYLENE VINYL ACETATE) - GAMASEPTO (NIM : 15007030); Pembimbing : Dr. Harmein Rahman S.T.,M.T., MARIO
A pavement structure is expected to have a good structural and functional performance, and also a long service life. This research aimed to compare the structural performance of a Stone Mastic Asphalt (SMA) mixture using Pen 60/70 asphalt with the one using Polymer Modified Asphalt Ã‚Â– Ethylene Vinyl Acetate (EVA). The utilization of EVA as an asphalt modifier on SMA mixture is expected to improve structural performance of the mixture. Laboratory testing is done by using the Marshall Test method to determine the optimum asphalt content (OAC) of each mixture. Testing continued with the Marshall Immersion method to determine the durability of the mixtures. OAC results obtained is 6.6% for the 60/70 pen asphalt with aggregate gradation D = 5mm; 5.6% for the 60/70 pen asphalt with aggregate gradation D = 22mm; 7% for the EVA 3% modified asphalt with aggregate gradation D = 5mm; and 6.1% for the EVA 3% modified asphalt with aggregate gradation D = 22mm. Marshall Immersion results show that with the addition of EVA 3% on the asphalt with the gradation D = 5mm will result in 97.63% of Index of Remaining Strength (IRS), much better than the Pen 60/70 asphalt mixture with 91.48% of IRS.